Software embarcado e os custos de transação no processo de decisão do estabelecimento dos locais de desenvolvimento: um estudo de caso na indústria de telecomunicações - Barros, Marconi Cantalice (Universidade Federal de São Carlos, 2014)
This work aims to carry out an exploratory study of the effects of the transaction costs inherent in the software development process in organizations decision about where to establish the location for this development. To achieve the objective proposed, assuming software development environment and the decentralized aspect of the activity that is promoted by large organizations in various places in the world and still supported in aspects present in Theory of transaction costs and also in the literature of Software development, the methodology adopted consists of a case study developed within a large organization of the telecommunications industry. The case study is built on a specific product transfer who became from the design Centre in India to the design Centre in Brazil. Quantitative data, such as indicators of product maintenance, and also qualitative ones as cultural aspects raised in the transfer project and by the organizations involved, delineate the observation approach and the counterpoint to theory. The results obtained show that, in addition to economic aspects, other relational order factors associated with transaction costs accompanying the software development activity exert a great influence on the process to determine which structure will house product development. The study may contribute for a better understanding of the processes of adaptation and the structuring of organizations in respect of their development structures in an environment increasingly diverse and geographically spread.
Keywords: Organização do trabalho; Custos de transação; Software - desenvolvimento; Transaction costs; Software development; ENGENHARIAS::ENGENHARIA DE PRODUCAO